The Use of Artificial Intelligence in the Education of Nursing Students - Smodiš, Marta; Pivač, Sanela; Kalender Smajlović, Sedina (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Artificial intelligence has brought about many changes in various areas, including the education of nursing students in higher education. The benefits of using artificial intelligence are seen in more efficient and productive learning, the possibilities of training through simulation and robotics. The use of artificial intelligence is based on ethical principles and standards, with a focus on fairness, privacy, security, accountability, control, accessibility and the avoidance of harm. The use of online tools such as ChatGPT in the education of nursing students has had a significant impact on learning outcomes in the teaching process. Therefore, attention needs to be paid to teaching artificial intelligence skills, exploring effective ways to maintain digital literacy and fundamentally addressing the potential risks and negative impacts when using artificial intelligence.